Assessing risks to paediatric patients: conversation analysis of situation awareness in huddle meetings in England. Issue 5 (27th May 2019) - Hayes, Jacqueline; Lachman, Peter; Edbrooke-Childs, Julian; Stapley, Emily; Wolpert, Miranda; Deighton, Jessica
Abstract : Objectives: To analyse the language and conversation used in huddles to gain a deeper understanding of exactly how huddles proceed in practice and to examine the methods by which staff members identify at-risk patients. Setting: Paediatric wards in four English hospitals, which were part of a 12-hospital cohort participating in the Situation Awareness for Everyone programme. Wards varied by geographical region and type of hospital. Participants: Paediatric staff on wards in four English hospitals. Design: Ethnomethodology and conversation analysis of recorded safety huddles. Methods: This study represents the first analysis of huddle interaction. All huddle meetings taking place on four wards across four different hospitals were audio recorded and transcribed. The research question examined was: how are staff identifying at-risk patients in huddles? The ethnomethodological conversation analytic approach was used to analyse the transcripts. Results: Huddlers made use of categories that allowed them to efficiently identify patients for each other as needing increased attention. Lexicon included the use of 'no concerns', 'the one to watch', 'watcher' and 'acute concerns'. Huddlers used the meetings to go beyond standardised indicators of risk to identify relative risk and movement in patients towards deterioration, relative to the last huddle meeting and to their usual practices. An implicit category, termed here 'pre-concerns', was used by staff to identify such in-between states. Sequential analysis also highlighted the conversational rights that were held implicitly by staff in different clinical roles. Conclusion: Practical implications and recommendations for huddlers are considered. These included that for increased situation awareness, it is recommended that all staff are active in the huddle conversation and not only the most senior team members.